Diagnostic accuracy of imaging brain vesicular monoamine transporter type 2 (VMAT2) in clinically uncertain parkinsonian syndrome (CUPS): a 3-year follow-up study in community patients. Issue 11 (15th November 2018) - Xu, San San; Alexander, Paschal K; Lie, Yenni; Dore, Vincent; Bozinovski, Svetlana; Mulligan, Rachel S; Young, Kenneth; Villemagne, Victor L; Rowe, Christopher C
Abstract : Objectives: To further validate the diagnostic utility of 18 F-AV-133 vesicular monoamine transporter type 2 (VMAT2) positron emission tomography (PET) in patients with clinically uncertain parkinsonian syndromes (CUPS) by comparison to clinical diagnosis at 3 years follow-up. Design, setting and participants: In a previous study, we reported that 18 F-AV-133 PET in community patients with CUPS changed diagnosis and management and increased diagnostic confidence. The current diagnosis of this cohort was obtained from the patient and treating specialist and compared with the diagnosis suggested 3 years earlier by the 18 F-AV-133 PET. A second 18 F-AV-133 PET was available in those with a discordant or inconclusive final diagnosis. Study outcome measures: The primary end point was the proportion of patients who had a follow-up clinical diagnosis, which was concordant with their initial 18 F-AV-133 PET scan. Secondary end points were the proportion of patients who had the same diagnosis at follow-up as that reached after the initial scan and the stability of diagnostic changes made after the first scan. Results: 81 of the 85 patients previously recruited to the CUPS study had follow-up of which 79 had a clinical diagnosis and 2 remained CUPS. The diagnosis was in agreement with the initial 18 F-AV-133 PET scan result in 74 cases. Five patients had a discordant diagnosis; one patient with rubral tremor had a severely abnormal scan that had worsened when rescanned; four cases with normal initial and repeat scans had a clinical diagnosis of Parkinson's disease. Two patients with suspected genetic disorders remained classified as CUPS and both had normal scans. In the 24 CUPS cohort patients where 18 F-AV-133 PET initially changed diagnosis, this change was supported by follow-up diagnosis in all but the one rubral tremor case. Conclusion: 18 F-AV-133 PET is a useful tool in improving diagnostic accuracy in CUPS providing results and diagnostic changes that remain robust after 3 years follow-up.